Extraction of Al–Si master alloy and alumina from coal fly ash (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Coal fly ash from coal power plants is a potential raw material for the production of alumina. An objective aluminothermic reduction method for the preparation of Al-Si master alloy from coal fly ash was investigated. The kinetic analysis using non-isothermal differential scanning calorimetry indicated that the reduction of Al6Si2O13, Fe2O3, and TiO2 by aluminum in coal fly ash occurs at 1618 K, 1681 K, and 1754 K, respectively. Moreover, the influence of reaction temperature on product composition was studied. The phases and morphologies of the products obtained by the aluminothermic reduction of coal fly ash at 1373-1773 K were analyzed by X-ray diffraction, scanning electron microscopy, and energy-dispersive spectroscopy, respectively. The results showed that the final products are mixtures of Al-Si alloy, alumina, and mullite. In contrast, the products obtained by aluminothermic reduction of coal fly ash in an electric arc furnace were separated Al-Si master alloy and oxides rich in alumina. In addition, the chemical compositions of alloys from different areas are 75.80-85.46 wt.% Al, 8.18-20.10 wt.% Si, 2.25-5.13 wt.% Fe, and 0.87-1.01 wt.% Ti.